2020
DOI: 10.1021/acs.jpcc.0c07996
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Conformational Isomerization of Fluorenone-Based Polycatenar in 2D Polymorphic Self-Assembly

Abstract: A fluorenone-based polycatenar consisting of a central 2,7-bis­((5-phenyl­thiophen-2-yl)­ethynyl)-9-fluorenone core and −OCH2– linked 3,4,5-tris­(dodecyloxy)­benzoate unit at both sides (FTQ) has been synthesized by using Sonogashira coupling reactions as key steps. FTQ molecule exhibits columnar liquid crystalline phase. The molecular self-assembled behavior at the solid/liquid interface is investigated by scanning tunneling microscopy (STM). With the decrease of solution concentration, three nanostructures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…When isomerization units, such as the azo and dithiophene, are contained in the π-conjugated rigid backbone, molecular conformational isomerization may occur. 6,8 For example, our previous paper has reported that the LC molecule (FTQ) with thiophene groups on both sides of the 9fluorenone core shows a concentration-dependent cis−trans isomerization phenomenon on the graphite surface. In addition, Wu et al reported that only the trans-conformation of polynorbornenes could form LCs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When isomerization units, such as the azo and dithiophene, are contained in the π-conjugated rigid backbone, molecular conformational isomerization may occur. 6,8 For example, our previous paper has reported that the LC molecule (FTQ) with thiophene groups on both sides of the 9fluorenone core shows a concentration-dependent cis−trans isomerization phenomenon on the graphite surface. In addition, Wu et al reported that only the trans-conformation of polynorbornenes could form LCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They make perfect candidates to investigate the molecular self-assembly behaviors and their mechanism. The typical chemical structure of LC molecules possesses a π-conjugated backbone, polar groups, and aliphatic chains. Therefore, the molecular shape and the intermolecular weak interactions play significant roles in controlling the stability of LCs. Several techniques have been used to study LC properties, such as X-ray diffraction, differential scanning calorimetry, polarized optical microscopy, and other common techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Conformational isomerism is a kind of stereoisomerism in which the atoms or clusters of organic molecules are arranged differently in space due to the rotation or distortion of C–C single bond. Some external facts such as visible light, temperature, and solution concentration , can switch the molecular conformation and further affect the arrangement of organic adlayers, which might have enormous potential for the development of molecular optoelectronic devices. In addition, scanning tunneling microscopy (STM) has been proven to be a powerful tool to visualize self-assembled structures at the molecular scale, , giving us a better understanding of the molecular interactions of different conformations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we manage to control the self-assembled nanostructures of the molecules on the two-dimensional surface by adjusting the solution concentration and the type of solvent. This kind of long core liquid crystal molecule are rarely reported in the field of 2D molecular self-assembly relatively. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation